Pencerobohan tanah kerajaan bagi tujuan pertanian (kajian kes : Daerah Batu Pahat) - Supaat @ Supaa, Khasanah (2009)
The illegally encroachment issue of government land has always being an issue regarding matters of lands. This crime always happen not just at the rural areas but also happens in urban area. It also happens to government lands for agriculture purposes. This lands encroachment for agriculture purposes happens not just because poverty but also taking chances due to lack of attention from the responsible party. In this matters, lands that are not develops and lands that are not properly care are the main targets by the intruders. Those intruders will explore and work those lands without thinking the effects of it in law matters, just for achieving their goals and purposes for their own interests. Even though enforcement actions to this intruders activity for agriculture purposes have been taken, but the effects of it still unachievable. Because of that matters, this research is made for the purpose of identifying government lands invasion activity that happens in the district of Batu Pahat and identify what is that causes government lands invasion activity for agriculture purposes happens. At the same time, this research also been made to see enforcement actions that been made for this government lands invasion activity for agriculture purposes. Hopefully from this research, the District land office of Batu Pahat will issue a law or circular about the fines that will be imposed to individuals that involved in illegal activity of intruding government lands. Except that, hopefully this research will give benefits and exposure to the parties involved in preventing this activities from increase further.